The application of taḥawwul (transformation) process for determination of vinegar status in the Malaysia market - Harahap, I.; Muhamad Shukri, Abdul Salam @ Zulkifli; Jamaludin, Mohammad Aizat; Mohammad Nawawi, Norazah; Alias, R.; Zaharim, Azami (Rynnye Lyan Resources, 2020)
Taḥawwul is a changing process of a form to another form thus could affect the status of a particular ḥukm especially in vinegar products. Vinegar which produced before the taḥawwul ṣaḥīḥ can be considered as low-quality vinegar and is classified as fasīd vinegar (ḥarām) due to the presences of alcohol which is prohibited in Islam. Therefore, in this study, twenty-five different types of vinegar in Malaysian market were tested using Gas Chromatography attached with Flame Ionization Detector (HS-GC-FID) with Head Space Analyzer (HS-10) and Gas Chromatography (GC) with time of flight mass spectrometry (TOF-MS) to find out the contents of alcohol and acetic acids present in the said vinegar products. The results showed that majority of the sample were ḥalāl. However, there were two types of vinegar that were not considered ḥalāl because these products did not go through a complete process of (taḥawwul ṣaḥīḥ).